Islam Terhadap Misi Pendidikan - Azis, Rosmiaty (Inspiratif Pendidikan, 2016)
One of Islamic objectives is related to the desired change in the process of education in Islam dealing with the improvement of human resources for students themselves, the community or the environment of where they live. Among purposes should be clear, so that education in Islam can be measured its success step by step. Then, the mission of education in Islam, namely the achievement of a whole person and the happiness of the world and the hereafter, requires human consciousness to serve and fear to God and strengthen ukhuwah islamiyah (the concept of brotherhood in Islam) among Muslims and the establishment of a real human being. It does not mean letting people in doubt and heresy in establishing their selves on their own individual willingness. However, it deals with the formation of clear characteristics through a strategy that really steady. The characteristic of the real human beings is a man who has a high degree of knowledge and always prays to God. It is different with the unlimited sense of multi-dimensional problems of life that are covering all activities in the relation to the individual and social which is based on Islamic values.